Pelatihan Penyusunan Proposal Penelitian dan Pengabdian untuk Dosen STIEBI Syaikhona Kholil Sidogiri Pasuruan - ST. Ulfawanti Intan Subadra; Sri Rahmawati; Aji Prasetya Wibawa; RR. Poppy Puspitasari; Nurul Hidayat; Ahmad Taufiq (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Research and community service are part of the Tri Dharma of Higher Education that must be carried out by a lecturer. In fact, the Government has provided funds for lecturers to carry out research and community service. However, low motivation, interest, and knowledge in writing are some of the reasons why lecturers do not write proposals. Therefore, the community service team conducted training on writing research and community service proposals for lecturers at the Syaikhona Kholil Islamic Economics and Business College, Pasuruan. The training was conducted using lecture and direct practice methods, and was divided into three sessions. The evaluation results showed that 100% of participants stated that the material presented was in accordance with the needs of the participants and the strategies used in the training were very effective. This activity had a positive impact on lecturers' motivation in writing proposals. In addition, knowledge and ability in using the Zotero reference manager also increased, making it easier for STEIBI Syaikhona Kholil lecturers to write references both in proposals and in scientific articles.